Bidirectional Associations Between Depressive and Anxiety Symptoms and Loneliness During the COVID-19 Pandemic: Dynamic Panel Models With Fixed Effects - McDowell, Cillian P.; Meyer, Jacob D.; Russell, Daniel W.; Sue Brower, Cassandra; Lansing, Jeni; Herring, Matthew P. (Frontiers in Psychiatry, 2021)
Background Understanding the direction and magnitude of mental health-loneliness associations across time is important to understand how best to prevent and treat mental health and loneliness. This study used weekly data collected over eight weeks throughout the COVID-19 pandemic to expand previous findings and using dynamic panel models with fixed effects which account for all time-invariant confounding and reverse causation. Methods Prospective data on a convenience and snowball sample from all 50 US states and the District of Colombia (n=2361 with ≥2 responses, 63.8% female; 76% retention rate) were collected weekly via online survey at nine consecutive timepoints (April 3-June 3, 2020). Anxiety and depressive symptoms and loneliness were assessed at each timepoint and participants reported the COVID-19 containment strategies they were following. Dynamic panel models with fixed effects examined bidirectional associations between anxiety and depressive symptoms and loneliness, and associations of COVID-19 containment strategies with these outcomes. Results Depressive symptoms were associated with small increases in both anxiety symptoms (β=0.065, 95%CI=0.022–0.109; p=0.004) and loneliness (β=0.019, 0.008–0.030; p=0.001) at the subsequent timepoint. Anxiety symptoms were associated with a small subsequent increase in loneliness (β=0.014, 0.003–0.025; p=0.015) but not depressive symptoms (β=0.025, -0.020–0.070; p=0.281). Loneliness was strongly associated with subsequent increases in both depressive (β=0.309, 0.159–0.459; p<0.001) and anxiety (β=0.301, 0.165–0.436; p<0.001) symptoms. Compared to social distancing, adhering to stay-at-home orders or quarantining were not associated with anxiety and depressive symptoms or loneliness (both p≥0.095). Conclusions High loneliness may be a key risk factor for the development of future anxiety or depressive symptoms, underscoring the need to combat or prevent loneliness both throughout and beyond the COVID-19 pandemic. COVID-19 containment strategies were not associated with mental health, indicating that other factors may explain previous reports of mental health deterioration throughout the pandemic.